Kinetic Study on the CsXH3−X PW12O40/Fe-SiO2 Nanocatalyst for Biodiesel Production - Mostafa Feyzi; Leila Norouzi; Hamid Reza Rafiee (The Scientific World Journal)
The kinetic of the transesterification reaction over the CsXH3−XPW12O40/Fe-SiO2 catalyst prepared using sol-gel and impregnation procedures was investigated in different operational conditions. Experimental conditions were varied as follows: reaction temperature 323–333 K, methanol/oil molar ratio = 12/1, and the reaction time 0–240 min. The H3PW12O40 heteropolyacid has recently attracted significant attention due to its potential for application in the production of biodiesel, in either homogeneous or heterogeneous catalytic conditions. Although fatty acids esterification reaction has been known for some time, data is still scarce regarding kinetic and thermodynamic parameters, especially when catalyzed by nonconventional compounds such as H3PW12O40. Herein, a kinetic study utilizing Gc-Mas in situ allows for evaluating the effects of operation conditions on reaction rate and determining the activation energy along with thermodynamic constants including ΔG, ΔS, and ΔH. It indicated that the CsXH3−XPW12O40/Fe-SiO2 magnetic nanocatalyst can be easily recycled with a little loss by magnetic field and can maintain higher catalytic activity and higher recovery even after being used 5 times. Characterization of catalyst was carried out by using scanning electron microscopy (SEM), X-ray diffraction (XRD), Fourier transform-infrared spectroscopy (FT-IR), N2 adsorption-desorption measurements methods, thermal gravimetric analysis (TGA), and differential scanning calorimetry (DSC).